Review: A Safety Profile of Dalbavancin for On- and Off-Label Utilization - Simonetti O (Dove Medical Press, 2021)
Oriana Simonetti,1,* Giulio Rizzetto,1,* Elisa Molinelli,1 Oscar Cirioni,2 Annamaria Offidani1 1Clinic of Dermatology, Department of Clinical and Molecular Sciences, Polytechnic University of Marche, Ancona, Italy; 2Clinic of Infectious Diseases, Department of Biomedical Sciences and Public Health, Polytechnic University of Marche, Ancona, Italy*These authors contributed equally to this workCorrespondence: Oriana SimonettiDermatological Unit, Department of Clinical and Molecular Sciences, Polytechnic Marche University, Via Conca 71, Ancona, 60126, ItalyEmail o.simonetti@staff.univpm.itIntroduction: Dalbavancin is a bactericidal lipoglycopeptide active against gram-positives. Its use has been approved for the treatment of acute bacterial skin and skin structure infections (ABSSSI).Methods: We conducted a narrative review of the literature on the safety profile of dalbavancin. The bibliographic research was carried out on the PubMed database on 6 November 2020 by seeking combinations of the following keywords: dalbavancin, adverse effects, safety, drug interactions, and skin infections.Results: Five double-blind Phase 3 randomized clinical trials, 2 open-label randomized trials, and 4 retrospective studies were identified. No statistically significant differences were found between dalbavancin and comparators in the incidence of adverse events. Retrospective studies confirm the low incidence of adverse events.Conclusion: Dalbavancin is a therapeutic option that has demonstrated an excellent safety profile, also in relation to the other MRSA therapies available. Its use represents a cost-effective solution for the treatment of those patients with ABSSSI who would need hospitalization. One limitation of this study is that most of the available data are from Phase III clinical trials. Further real-life studies with a larger sample size are therefore needed to better assess the safety profile of the dalbavancin, especially to investigate the true incidence of rare adverse events.Keywords: dalbavancin, adverse events, safety, skin infections, ABSSSI